골절 치유 과정에서 HIF-1α와 VEGF의 발현 - 김정재(Jung-Jae Kim); 손현철(Hyun-Chul Shon); 장재석(Jae-Suk Chang); 김정화(Jung-Hwa Kim); 이강식(Kang-Sik Lee); 김석원(Seok-Won Kim) (The journal of the Korean Orthopaedic Association, 2008)
Purpose: To elucidate the relation between fracture healing and angiogenesis, we checked expression of Hypoxia-inducible factor (HIF) and Vascular endothelial growth factor (VEGF) in hypoxic cell cultures and the callus from a rat femur fracture model. Materials and Methods: Human osteoblasts, chondrocytes, and rat ST2 cells were cultured in DME/F12 media with 10% FBS. Hypoxic DME/F12 media (PO2＜60 mmHg) was generated by bubbling with 95% N2 and 5% CO2 and added to cells. After 2, 6, and 24 hours, RNA and proteins were collected for reverse transcription - polymerase chain reaction (RT-PCR) and Western blot. In addition, immunocytochemistry and siRNA treatment for HIF-1α were performed. Next, femurs from 9-week SD rats were fractured after fixation with needles. The rats were sacrificed at post-fracture day (PFD) 3, 5, 7, 10, 14, 21 and calluses were collected for RT-PCR and Western blot. Results: HIF-1α and HIF-2α expression were not increased in RT-PCR but protein levels were increased. VEGF expression in RT-PCR was increased. Treatment with siRNA directed towards HIF inhibited VEGF expression. In the rat fracture callus, HIF-1α and VEGF expression peaked between PFD 5 and 7 and decreased after PFD 10. In contrast to cell culture, mRNA expression of HIF-1α was increased at PFD 7. Conclusion: HIF-1α and VEGF peaked early in fracture healing. With expression decreasing as O2 tension increased. Further study is needed to identify other factors affecting chondrogenic differentiation. KCI Citation Count: 2